Conscience reconsidered: The moral work of navigating participation in abortion care on labor and delivery. (July 2019) - Czarnecki, Danielle; Anspach, Renee R.; De Vries, Raymond G.; Dunn, Mercedez D.; Hauschildt, Katrina; Harris, Lisa H.
Abstract: How do caregivers make decisions about participating in morally contested care, such as abortion? Debates about conscience in the delivery of health care generally assume that participation decisions stem from religious beliefs and moral values. Few studies have examined this question in the context of everyday practice. Drawing on 50 interviews with the staff of a labor and delivery unit offering abortion care—including nurses, maternal-fetal medicine specialists, obstetrics and gynecology residents, and anesthesiologists—we show that respondents have varied definitions of "participation" in abortion care and that participation decisions are driven by an array of factors beyond personal beliefs. We present a conceptual model of "moral work" that shows conscience to be an emerging, iterative process influenced not only by beliefs—religious and non-religious—but also by personal and work experiences and social and institutional contexts. Our study brings new insights into understanding conscience and participation in contested care. Highlights: Caregivers' experiences force us to rethink conscience and participation in abortion care. Factors beyond religious and moral values shape abortion care participation decisions. Caregivers have varied definitions of "participation" in abortion work. Participation decisions are an iterative process of "moral work" in abortion care. Religious beliefs can motivate the provision of abortion care, not just refusal.